Maryport : a Roman fort and its community - Breeze, David J. (Archaeopress Publishing Ltd, 2018)
The collection of Roman inscribed stones and sculpture, together with other Roman objects found at Maryport in Cumbria, is the oldest archaeological collection in Britain still in private hands. David Breeze places the collection in context and describes the history of research at the site